Penetapan Pidana Tidak Dijalani Dalam Perbuatan Melakukan Kekerasan Terhadap Anak - Nurkholim Nurkholim; Dandi Mulyana (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study discusses the imposition of suspended prison sentences (conditional sentences) in cases of violence against children based on the Bangka Belitung High Court Decision Number 33/Pid.Sus/2020/PT BBL. The study focuses on the judges' considerations underlying the imposition of suspended sentences and their compatibility with the principles of child protection in Law No. 35 of 2014. The results of the study show that the judges used Article 14a of the Criminal Code, which allows for suspended sentences if the penalty is not more than one year and the defendant has no previous convictions. Mitigating considerations included the defendant's confession, remorse, and his profession as a teacher. However, from a child protection perspective, this verdict poses a dilemma because it risks reducing the deterrent effect and has the potential to set a precedent that violence against children can be tolerated. Legal and sociological analysis shows that although suspended sentences are legally valid, their application is not fully in line with the principle of the best interests of the child and the objectives of criminal punishment, which emphasise justice and victim protection. Therefore, a more assertive legal policy is needed so that all forms of violence against children are treated as serious crimes that cannot be compromised.